Crystallizing the hypoplactic monoid: from quasi-Kashiwara operators to the Robinson-Schensted-Knuth-type correspondence for quasi-ribbon tableaux - Cain, Alan J. (2019)
FCT fellowship (IF/01622/2013/CP1161/CT0001).